2023
DOI: 10.47852/bonviewjdsis32021067
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Facial Mask Using Deep Learning Classification Algorithm

Abstract: Machine Learning is increasingly popular among the public because of the many devices that are made using the capabilities of Machine Learning algorithms. Machine Learning's ability to process and analyze data quickly and accurately, as well as generate useful and relevant information for users, is the main reason for its popularity. Many machine learning algorithms have been used to solve various problems in society, including Deep Learning (DL). Deep Learning is an algorithm that works by representing data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…The dendritic neural model (DNM) is better able to handle uncertainty in data and may, in this way, improve the memory function of the model [23]. At the same time, the algorithms used now are also improved and optimized, either through distributed parallel cooperative co-evolution particle swarm optimization (DPCCPSO) [24], where the inertia weights and learning factors are adjusted during the evolutionary process, or through deep learning, eliminating the requirement for manual feature engineering [25]. The purpose of analyzing the cable is achieved by converting the measured data into images using window-based convolutional neural network (CNN), integrated recurrent neural network (RNN), and autoen- In Figure 15, it can be observed that the results predicted by the neural network model have a higher accuracy than the results calculated using the formulas mentioned in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The dendritic neural model (DNM) is better able to handle uncertainty in data and may, in this way, improve the memory function of the model [23]. At the same time, the algorithms used now are also improved and optimized, either through distributed parallel cooperative co-evolution particle swarm optimization (DPCCPSO) [24], where the inertia weights and learning factors are adjusted during the evolutionary process, or through deep learning, eliminating the requirement for manual feature engineering [25]. The purpose of analyzing the cable is achieved by converting the measured data into images using window-based convolutional neural network (CNN), integrated recurrent neural network (RNN), and autoen- In Figure 15, it can be observed that the results predicted by the neural network model have a higher accuracy than the results calculated using the formulas mentioned in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The precision and accuracy of an acoustic-based DoA estimation are essential across a spectrum of industries, spanning vital applications in both civilian and military sectors. Encompassing critical domains such as defense, law enforcement, security [1], and surveillance [2], reliable and precise DoA estimation ensures safety, strategic decision-making [3], and operational effectiveness. Applications such as gunshot DoA estimation [4], drone DoA estimation [5], and automotive angle estimation [6] require highly accurate estimates for optimal functionality.…”
Section: Introductionmentioning
confidence: 99%